Building the forecasting system of decision-making in cloud computing - Nguyen, Tan Thuan (Trường Đại học Đà Lạt, 2014)
This paper describes the forecasti ng sy stem of decision-making on cloud computing by applying the algorithm C4 .5. This paper focus on the visualized software solution with th e pur pose of providing multiple services in the fields of business, commerce, ed ucation, health, tourism, etc. by collecting data via internet and building decision tree to -pred ict forecast report to user through the algorithm C4.5. This paper mainly highlights di fferent methods and decisions within the system by many criteria, subdivisions, processes, and other features of C4.5 . The paper describes the C4.5 as the opt im ized algorithm through the d ivi s ion standard of classification in which the Information Gain is used as the criter ia for eva luating algorithm C4 .5.